2007
DOI: 10.1037/0022-0663.99.2.397
|View full text |Cite
|
Sign up to set email alerts
|

Spatial ability: A neglected dimension in talent searches for intellectually precocious youth.

Abstract: Students identified by talent search programs were studied to determine whether spatial ability could uncover math-science promise. In Phase 1, interests and values of intellectually talented adolescents (617 boys, 443 girls) were compared with those of top math-science graduate students (368 men, 346 women) as a function of their standing on spatial visualization to assess their potential fit with math-science careers. In Phase 2, 5-year longitudinal analyses revealed that spatial ability coalesces with a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
148
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(164 citation statements)
references
References 98 publications
(154 reference statements)
12
148
0
4
Order By: Relevance
“…The former reflect stable and deep-rooted differences between men and women in their preferences for particular types of tasks, but especially for caring, nurturing, and interactin g with people as opposed to objects. Ceci et al (2009) provide no new evidence in support of this essentiali st claim, but their interpretive review identifies ''pronounced sex differences in occupationa l preferenc es that occur along a 'people-to-obje ct' dimension (Lippa, 1998 ): Women are more likely to pursue people-oriented or organic fields, whereas men with similar mathematics and science ability tend to pursue object-orien ted fields (Webb et al, 2007 ;see Lippa, 2005 , for a review).'' The research reported in these citations 4 Not all STEM majors wind up in STEM occupations (see, e.g., Sassler et al, n.d.); and, conversely, some pathways into the science pipeline emerge late in educational careers (Xie and Shauman, 2003 ).…”
Section: Pipeline and Life Course Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The former reflect stable and deep-rooted differences between men and women in their preferences for particular types of tasks, but especially for caring, nurturing, and interactin g with people as opposed to objects. Ceci et al (2009) provide no new evidence in support of this essentiali st claim, but their interpretive review identifies ''pronounced sex differences in occupationa l preferenc es that occur along a 'people-to-obje ct' dimension (Lippa, 1998 ): Women are more likely to pursue people-oriented or organic fields, whereas men with similar mathematics and science ability tend to pursue object-orien ted fields (Webb et al, 2007 ;see Lippa, 2005 , for a review).'' The research reported in these citations 4 Not all STEM majors wind up in STEM occupations (see, e.g., Sassler et al, n.d.); and, conversely, some pathways into the science pipeline emerge late in educational careers (Xie and Shauman, 2003 ).…”
Section: Pipeline and Life Course Modelsmentioning
confidence: 99%
“…10 In one of the few excepti ons, Legewie and DiPrete (2012) offer an analysis of the NELS data that includes students' early ''STEM orientatio n'' measure d with two indicators, one of which is a dummy variable from the NELS 8th grade occupation al plan 7 Lippa (2005) (1998), a 2002 internet survey with an unknown sampling design but with 30% of its respondents from California, and a dual convenience sample of Cal-State Fullerton students and participants in two gay pride festivals, all of whom agreed to participate in a study of finger-length ratios and sexual orientation. The Webb et al (2007) sample is ''precocious youth'' who (a) scored at or above the 97th percentile, and in many cases at or above the 99.5th percentile, in math or reading, (b) participated in a voluntary ''talent search'' program and associated enrichment activities, and (c) survived the longitud inal study's 48% attrition rate.…”
Section: Occupational Plans and College Major Selectionmentioning
confidence: 99%
“…Recent research on the ability profiles of participants in project TALENT has associated unique, domain-specific ability constellations of mathematical, spatial, verbal, and composite ability scores with specific academic domains (Wai et al, 2009;Webb, Lubinski, & Benbow, 2007). Longitudinal studies have supported the predictive validity of this constellation of abilities for completion of doctoral, master or bachelor degrees in STEM disciplines (Wai et al, 2009).…”
Section: Identification Of Stem Potentialmentioning
confidence: 99%
“…Spatial reasoning skills may be critical to scientific reasoning (Ganley, Vasilyeva, & Dulaney, 2014). Research indicates that spatial ability is significant for talent identification (Webb, Lubinski & Benbow, 2007). The studies by Lubinski on spatial ability for very high achievers show that "tilt" especially predicts STEM achievements (Lubinski, 2010).…”
Section: What Can We Do To Help Girls More Accurately Assess Their Abmentioning
confidence: 99%